2021
DOI: 10.3389/fmicb.2021.609840
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Resistance Among Multiple Sequence Types of Klebsiella pneumoniae Is Associated With Diverse Resistance Mechanisms: A Report From India

Abstract: Background: The resistance to colistin and carbapenems in Klebsiella pneumoniae infections have been associated with increased morbidity and mortality worldwide. A retrospective observational study was conducted to determine the prevalence and molecular events contributing to colistin resistance.Methods: Clinical samples were screened for colistin resistance and underlying mechanisms were studied by PCR-based amplification and sequence analysis of genes of two-component regulatory system (phoPQ and pmrAB), reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 69 publications
0
23
1
Order By: Relevance
“…Nucleotide position 75 represents a hotspot for IS5 element insertion among clonally unrelated K. pneumoniae isolates (Cannatelli et al, 2013; Poirel et al, 2014). Mobilization of IS5 elements from plasmids into the mgrB gene of colistin resistant K. pneumoniae has been speculated owing to the similarity between the IS5 element inserted into mgrB and the IS5 element present on K. pneumoniae carbapenemase (KPC)‐encoding and other Gram‐negative bacterial plasmids (Azam et al, 2021; Cannatelli et al, 2013; Hala et al, 2019), and endogenous presence of IS5‐like elements in the genome of colistin resistant K. pneumoniae (Choi & Ko, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nucleotide position 75 represents a hotspot for IS5 element insertion among clonally unrelated K. pneumoniae isolates (Cannatelli et al, 2013; Poirel et al, 2014). Mobilization of IS5 elements from plasmids into the mgrB gene of colistin resistant K. pneumoniae has been speculated owing to the similarity between the IS5 element inserted into mgrB and the IS5 element present on K. pneumoniae carbapenemase (KPC)‐encoding and other Gram‐negative bacterial plasmids (Azam et al, 2021; Cannatelli et al, 2013; Hala et al, 2019), and endogenous presence of IS5‐like elements in the genome of colistin resistant K. pneumoniae (Choi & Ko, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Bshabshe et al from Saudi Arabia showed 34.5% resistance to colistin [ 21 ]. Poudyal et al In Australia examined 21 MDR K. pneumoniae , of which 6 isolates were resistant to colistin (28.5%) [ 22 ].Other studies from India, Poland, Pakistan, and Spain reported 16, 0, 4.8 and 13% colistin resistance in K. pneumoniae isolates [ 23 26 ]. Although a similar meta-analysis is needed to compare the resistance of colistin to other countries, the study of resistance to this antibiotic in Iran showed a moderate resistance level compared to other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, other researchers have mentioned the deleterious L26Q substitution in the phoP gene [ 55 ]. Furthermore, some mutations closely related to those above were detected in the phoQ gene (such as L30Q, L26P, L96R, and L257P substitutions) [ 31 , 56 , 57 , 58 ] and the phoP gene (V3F) [ 58 ] and have previously been described as mediating colistin resistance.…”
Section: Discussionmentioning
confidence: 99%